APPLICATION OF OBJECT ORIENTED NEURAL NETWORK TO CONTROL MOTION OF THE LOAD OF A SEA CRANE - Falat, Pawel; Brzozowska, Lucyna; Brzozowski, Krzysztof (International Journal of Computing, 2014)
The paper presents object oriented approach to design of neural networks. The second part of the article presents an application of the object oriented neural network to control the load of the sea crane of an A-Frame type. The control algorithm has to stabilize load position and compensate the weaving. The model of the A-Frame dynamics were developed and used to achieve the optimal winch drive functions for various sea conditions. Those functions have been used to teach the network.